Mathematics and science teachers’ using of assessment techniques for learning in the classroom situation in basic education schools in the Sultanate of Oman - Alsaidi, Humaid Muslem; Alshidi, Khalid Juma (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the level of use of assessment techniques by mathematics and science teachers for learning in the classroom situation in basic education schools in the Sultanate of Oman. To achieve the objectives of the study, the researchers used the quantitative descriptive approach, by preparing a questionnaire consisting of (29) phrases distributed over three areas, and after verifying the validity and reliability of the tool, it was applied to a sample of (68) supervisors. The results of the study revealed that the level of mathematics and science teachers’ employment of assessment techniques for learning in the classroom situation in basic education schools in the Sultanate of Oman came with an average of (2.98) at an average level, where it came first: the level of employment level of teacher assessment techniques, and in the second place: The domain of the level of employment of peer evaluation techniques, and finally: the domain of the level of employment of self-evaluation techniques. The results also indicated that there were statistically significant differences between the level of mathematics and science teachers’ employment of assessment techniques for learning in the classroom situation in basic education schools in the Sultanate of Oman due to the gender variable in favor of females, and in specialization in favor of science teachers. The researchers recommended the need to reduce the administrative burden on mathematics teachers and reduce their shares, and increase the activation of viewing sessions in self-evaluation techniques and peer assessment techniques with skilled teachers, and activate the role of educational supervisors in following up the employment of assessment techniques for learning in the classroom situation.